Intermediate progenitors and Tbr2 in cortical development. Issue 3 (24th January 2019) - Hevner, Robert F.
Abstract: In developing cerebral cortex, intermediate progenitors (IPs) are transit amplifying cells that specifically express Tbr2 (gene: Eomes ), a T‐box transcription factor. IPs are derived from radial glia (RG) progenitors, the neural stem cells of developing cortex. In turn, IPs generate glutamatergic projection neurons (PNs) exclusively. IPs are found in ventricular and subventricular zones, where they differentiate as distinct ventricular IP (vIP) and outer IP (oIP) subtypes. Morphologically, IPs have short processes, resembling filopodia or neurites, that transiently contact other cells, most importantly dividing RG cells to mediate Delta‐Notch signaling. Also, IPs secrete a chemokine, Cxcl12, which guides interneuron and microglia migrations and promotes thalamocortical axon growth. In mice, IPs produce clones of 1–12 PNs, sometimes spanning multiple layers. After mitosis, IP daughter cells undergo asymmetric cell death in the majority of instances. In mice, Tbr2 is necessary for PN differentiation and subtype specification, and to repress IP‐genic transcription factors. Tbr2 directly represses Insm1, an IP‐genic transcription factor gene, as well as Pax6, a key activator of Tbr2 transcription. Without Tbr2, abnormal IPs transiently accumulate in elevated numbers. More broadly, Tbr2 regulates the transcriptome by activating or repressing hundreds of direct target genes. Notably, Tbr2 'unlocks' and activates PN‐specific genes, such as Tbr1, by recruiting Jmjd3, a histone H3K27me3 demethylase that removes repressive epigenetic marks placed by polycomb repressive complex 2. IPs have played an important role in the evolution and gyrification of mammalian cerebral cortex, and TBR2 is essential for human brain development.